Composition of Sedimentary Organic Matter across the Laptev Sea Shelf: Evidences from Rock-Eval Parameters and Molecular Indicators; Water; Vol. 12, iss. 12 - Gershelis E. V. Elena Vladimirovna; Grinko A. A. Andrey Alekseevich; Oberemok I. A. Irina Andreevna; Klevantseva E. V. Elizaveta Vasiljevna; Poltavskaya N. A. Natalina Aleksandrovna; Ruban A. S. Aleksey Sergeevich; Chernykh D. V. Denis Vyacheslavovich; Leonov A. A. Andrey Andreevich; Guseva N. V. Natalia Vladimirovna; Semiletov I. P. Igor Petrovich (2020, 2020)
Title screen